2014
DOI: 10.1073/pnas.1310355111
|View full text |Cite
|
Sign up to set email alerts
|

Unitary step of gliding machinery in Mycoplasma mobile

Abstract: Among the bacteria that glide on substrate surfaces, Mycoplasma mobile is one of the fastest, exhibiting smooth movement with a speed of 2.0-4.5 μm·s −1 with a cycle of attachment to and detachment from sialylated oligosaccharides. To study the gliding mechanism at the molecular level, we applied an assay with a fluorescently labeled and membrane-permeabilized ghost model, and investigated the motility by high precision colocalization microscopy. Under conditions designed to reduce the number of motor interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 36 publications
2
74
0
Order By: Relevance
“…In previous studies, the addition of free SL decreased the number of legs binding to the SOs on glass and enabled the observation of cell pivoting (23) and stepwise cell displacements (24). In the present study, we found that 70% and 30% of cells glided to the left and the right, respectively, in the presence of 250 M SL (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In previous studies, the addition of free SL decreased the number of legs binding to the SOs on glass and enabled the observation of cell pivoting (23) and stepwise cell displacements (24). In the present study, we found that 70% and 30% of cells glided to the left and the right, respectively, in the presence of 250 M SL (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…However, if the number of working legs is decreased, it may be possible to detect the propulsion force generated by a single unit (24,34). Previous studies showed that the number of working legs can be decreased by adding free SOs (21)(22)(23)(24). We therefore added various concentrations of free sialyllactose (SL), an SO, to gliding M. mobile cells and analyzed their gliding ( a lower frequency (Fig.…”
Section: Gliding Directionmentioning
confidence: 99%
See 3 more Smart Citations